The Efforts to Resolve the Prolonged South China Sea Conflict According to the perspective of the United Nations Convention on The Law of the Sea (UNCLOS) - Mauludina, Resya; Sulistiara, Wellinda Rizka; Redjosari, Slamet Muliono (Jurnal Hubungan Internasional Indonesia, 2023)
The power struggle in the South China Sea region has become an important topic of public discussion. Several ASEAN countries, including Indonesia, as well as the influence of the United States and Chinese powers, are strategically competing for maritime trade routes and rich potential resources. This study aims to analyze the geopolitical phenomena in the South China Sea region. Since 2010, when China claimed Indonesia’s exclusive economic zone in the northern part of the Natuna Islands, Indonesia has been "dragged" in the South China Sea dispute. China’s unilateral claims continued and peaked in 2016 when Chinese fishing boats carried out illegal fishing in the Natuna waters. This study aims to provide direction and recommendations for the conflict. The study is analyzed using qualitative methods and the concepts of national interest, geopolitics, and geostrategy. The results of the study show that conflicts in the South China Sea have not yet surfaced, because many parties still insist on defending the territorial sovereignty of the South China Sea.